STUDI PERBEDAAN TINGKAT SELF REGULATED LEARNING DITINJAU DARI SPIRITUAL WELL BEING PADA SISWA DI SEKOLAH BERBASIS PESANTREN DAN NON PESANTREN - Lisnawati Lisnawati (UIN Sunan Kalijaga, 2013)
This present research is focused on determining whether there is a difference Self Regulated Learning (SRL), when viewed from the Spiritual Well Being, between students in boarding school-based and non- boarding. The study sample consisted of each of a number of 33 respondents from boarding and non- boarding school. The total number of respondents was 66. Measuring instruments used is Scale SRL and Spiritual Well Being Scale. The results showed that there was no difference in the level of SRL in terms of Spiritual Well Being, between students from boarding school-based and non-boarding. In addition, the results also show that there is a relationship between variables SRL with variable Spiritual Well Being. The higher level of Spiritual Well Being, the ability of students is also higher SRL. Conversely, the lower the Spiritual WellBeing, then the lower the students’ ability SRL. It was concluded that, the aspects contained in the Spiritual Well Being will help students to have a good ability SRL. The absence of differences by type of school is because the non-boarding school samples, that became the subject of research, has been practically apply aspects of spirituality in everyday learning situations at school. In addition, it is important to know how the SRL and Spiritual Well Being condition of the respondents in both groups, before they are educated in their respective schools.